Balancing autonomy and benefit in research ethics. - Fielder, J.H (IEEE Engineering in medicine and biology magazine)
Laws requiring motorcycle riders to wear helmets save lives and prevent nasty brain injuries. However, a substantial number of riders resent this parentalism and want to be free to decide whether to ride without a helmet and take the additional risk. After all, motorcycle riders have already chosen a more risky form of transportation. The debate is a conflict about which of two legitimate values should prevail: benefits to riders or freedom to choose. It is a debate that occurs whenever government restricts liberty in the name of social benefit. One of the places this debate takes place is in medical research. Our discussions about the ethics of research take place in the shadow of the Nazi medical atrocities in World War II. In this essay I explore the issue of clinical trials on human volunteers for whom there will be no anticipated benefit. The topic reveals how difficult it is to reconcile autonomy and protection of human volunteers.